1974
DOI: 10.1139/z74-120
|View full text |Cite
|
Sign up to set email alerts
|

Body-rubbing, marking, and other scent-related behavior in some ground squirrels (Sciuridae), a descriptive study

Abstract: In some ground squirrels, mainly Arctic and Columbian, body-rubbing can be comfort or marking behavior, depending on the context. The mouth-corner apocrine glands are probably involved in individual/group/mother–offspring recognition. These glands are also rubbed against the substrate, particularly by dominant males. This is apparently scent-marking and seems to express territorialism, dominance, and readiness to fight, particularly when accompanied by clawing of the ground, for the latter case. Marking is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 43 publications
0
35
1
Order By: Relevance
“…Such odors may allow males and females, which do nest together during the breeding season (Madison and McShea 1987), to locate one another more easily, to facilitate assessment of the groomer's odor by nearby opposite-sex conspecifics, and/or to coordinate breeding (Gosling 1990;Gosling and Roberts 2001;Witt et al 1988Witt et al , 1990Paz-y-Miño et al 2002). A similar inference could be drawn from studies that showed that male prairie voles (Ferkin et al 2001), ground squirrels (Steiner 1973(Steiner , 1974, rats (Wiepkema 1979), and hedgehogs (Brockie 1976) spend more time self-grooming when they encounter opposite-sex conspecifics as compared to same-sex conspecifics. We speculate that during the breeding season, self-grooming may be a type of stimulatory or anticipatory response triggered by the scent marks of reproductively active opposite-sex conspecifics.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Such odors may allow males and females, which do nest together during the breeding season (Madison and McShea 1987), to locate one another more easily, to facilitate assessment of the groomer's odor by nearby opposite-sex conspecifics, and/or to coordinate breeding (Gosling 1990;Gosling and Roberts 2001;Witt et al 1988Witt et al , 1990Paz-y-Miño et al 2002). A similar inference could be drawn from studies that showed that male prairie voles (Ferkin et al 2001), ground squirrels (Steiner 1973(Steiner , 1974, rats (Wiepkema 1979), and hedgehogs (Brockie 1976) spend more time self-grooming when they encounter opposite-sex conspecifics as compared to same-sex conspecifics. We speculate that during the breeding season, self-grooming may be a type of stimulatory or anticipatory response triggered by the scent marks of reproductively active opposite-sex conspecifics.…”
Section: Discussionmentioning
confidence: 82%
“…We do know that voles and other mammals spend different amounts of time engaged in self-grooming when they encounter the scents of particular conspecifics (Steiner 1973(Steiner , 1974Brockie 1976;Wiepkema 1979;Leonard et al 2005;Ferkin 2005;Ferkin and Leonard 2005). It is possible that the amount of time they do so may reflect the type or the nature of interaction that groomers would have with those conspecifics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Field and laboratory observations also suggest that many marking behaviors develop at puberty and, in some species, show seasonal fluctuations that correspond closely to changes in gonadal activity (see discussions by Mykytowycz, 1970;Steiner, 1974;Thiessen & Rice, 1976). Most of the developmental data, though, are not detailed.…”
Section: Pubertal and Seasonal Changes In Scent-markingmentioning
confidence: 99%